2012
DOI: 10.1007/s00204-012-0911-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FANCD2 deficiency on formaldehyde-induced toxicity in human lymphoblastoid cell lines

Abstract: Formaldehyde (FA), a major industrial chemical and ubiquitous environmental pollutant, has recently been classified by the International Agency for Research on Cancer as a human leukemogen. The major mode of action of FA is thought to be the formation of DNA-protein crosslinks (DPCs). Repair of DPCs may be mediated by the Fanconi anemia pathway; however, data supporting the involvement of this pathway is limited, particularly in human hematopoietic cells. Therefore, we assessed the role of FANCD2, a critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Sensitivity to formaldehyde and other aldehydes has been observed in a variety of cell lines with deficiencies in FA proteins. 32 33 40-43 900677A cells, with or without complementation by XRCC2, display no defect in FANCD2 monoubiquitination or foci formation. Since monoubiquitination of FANCI by the FA core complex is essential for FANCD2 monoubiquitination and assembly into foci, 15 16 FANCD2 is a reliable indicator that XRCC2 does not function early in the FA-BRCA pathway, but instead functions late.…”
Section: Discussionmentioning
confidence: 98%
“…Sensitivity to formaldehyde and other aldehydes has been observed in a variety of cell lines with deficiencies in FA proteins. 32 33 40-43 900677A cells, with or without complementation by XRCC2, display no defect in FANCD2 monoubiquitination or foci formation. Since monoubiquitination of FANCI by the FA core complex is essential for FANCD2 monoubiquitination and assembly into foci, 15 16 FANCD2 is a reliable indicator that XRCC2 does not function early in the FA-BRCA pathway, but instead functions late.…”
Section: Discussionmentioning
confidence: 98%
“…DPC are lost by spontaneous hydrolysis which can induce mutations [Quievryn and Zhitkovich, 2000]. The FANC-BRCA pathway is essential to counteract DPCs caused by FA [Jacquemont and Taniguchi, 2007;Ridpath et al, 2007;Ren et al, 2013] and genetic variants in these genes could influence individual susceptibility to develop leukemia. Recent studies in primary lung fibroblasts and lung epithelial cells showed that FA-induced DPC, but not DNA-adducts, triggered an S-phase-dependent p53-mediated stress response through a replication inhibition due to stalling of replicative helicases by the intact, superbulky DPC [Wong et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a tolerance pathway also exists, allowing replication across unrepaired DPX lesions that may include strand breaks (potentially causing genomic rearrangements) followed by strand ligation (Stingele et al 2015). Not least, the Fanconi anaemia pathway is important in the repair of inter-strand DNA cross-links and DPX (Ren et al 2013; Kirsch-Volders et al 2014; McHale et al 2014; Schneider et al 2015). …”
Section: Genotoxicitymentioning
confidence: 99%